The Impact of Tax Planning and Deferred Tax Expenses on Earnings Management: Moderation by COVID-19 - Sambuaga, Elfina Astrella; Liman, Caroline (Journal of Business And Entrepreneurship, 2025)
This study investigates the influence of tax planning and deferred tax expenses on earnings management, with a focus on the moderating effect of COVID-19. Using a sample of 72 companies in the materials and consumer staples sectors listed on the Indonesia Stock Exchange from 2018 to 2021, the study employs a quantitative approach with purposive sampling. The findings reveal that tax planning positively affects earnings management, indicating that companies engage in tax planning to reduce their tax burden by lowering reported profits. However, deferred tax expenses and COVID-19 do not significantly influence earnings management. Interestingly, COVID-19 weakens the relationship between tax planning and earnings management but does not affect the relationship between deferred tax expenses and earnings management. The study highlights several limitations, including issues with normality, multicollinearity, and heteroscedasticity tests, the use of only two independent variables, and the limited scope of company sectors and research periods. Future research should consider expanding the data set, adding more variables, and including a broader range of sectors and periods to achieve more comprehensive results.